Anthropometric and performance measures for the development of a talent detection and identification model in youth handball - Mohamed, H.; Vaeyens, R.; Matthys, S.; Multael, M.; Lefevre, J.; Lenoir, M.; Philippaerts, R. (Journal of Sports Sciences, 2009)
The first part of this study examined in which basic morphological and fitness measures Under-14 (n = 34) and Under-16 (n = 47) male youth handball players differ from reference samples of the same age (n = 430 and n = 570, respectively). To help develop a talent identification model, the second part of the study investigated which specific morphological and performance measures describe differences between elite (n = 18) and non-elite (n = 29) Under-16 youth handball players. The results showed that Under-16 handball players were significantly taller than the reference group; this was not the case in the Under-14 age group. Physical fitness in handball players was significantly better than in the reference groups. Multivariate analysis of covariance (maturation and chronological age as covariates) showed that the Under-16 elite players were heavier and had greater muscle circumferences than their non-elite peers. Elite players scored significantly better on strength, speed and agility, and cardiorespiratory endurance but not on balance, upper limb speed, flexibility or upper body muscular endurance. Maturation was a significant covariate in anthropometric measures but not in physical performance. Discriminant analysis between elite and non-elite players revealed that height, running speed, and agility are important parameters for talent identification. Specific anthropometric measures, in addition to some performance measures, are useful for talent identification in youth handball.